Transferring performance-based financing practices in Burundi health system: the role of actors’ interactions - Ndayishimiye, Richard; Niyondiko, Dominique (International Journal Of Community Medicine And Public Health, 2021)
Background: For the past twenty years, African countries have experienced a massive deployment of performance-based financing practices within health systems. These numerous transfers involved several actors of different profiles and who intervened at different levels. At a time when many actors in their diversity are playing key role in the success or failure of the transfer process, the role of actors’ interactions in the transfer process of performance-based financing practices remains however less explored in context and in depth. This paper aimed to explore the role of actors’ interactions in the deployment of this process within Burundi health system. Methods: We conducted a case study of the transfer of performance-based financing practices within Burundi health system. 32 semi-structured interviews were carried out in addition to documentary technique and observation. In a qualitative approach, our interpretive approach followed an abductive reasoning to interpret the data collected. Conceptualization using NVivo12 software allowed to perform thematic and content analysis. Results: We argued that the transfer setting, the organizational specifics, the nature of the transferred practices, the levels of operationalization and the actors’ perceptions are determining factors of the deployment of the transfer process of performance-based financing practices. Moreover, the actors’ interactions as well as their causes and their effects affect the deployment of the transfer process. Conclusions: The actors’ interactions are shown to play moderating and mediating roles in the process of transferring those practices. Future research could focus on verifying and validating this role with quantitative methods.